2018
DOI: 10.3390/molecules23112782
|View full text |Cite
|
Sign up to set email alerts
|

Partial Purification, Identification, and Quantitation of Antioxidants from Wild Rice (Zizania latifolia)

Abstract: To provide further insights into the potential health-promoting antioxidants from wild rice (Zizania latifolia), which is an abundant but underutilized whole grain resource in East Asia, a partial purification based on D101 macroporous resin was carried out for the purification and enrichment of the antioxidants from the bioactive ethanol extracts of wild rice. On that basis, 34 phenolic compounds in the antioxidant fractions were identified by a high-performance liquid chromatography-linear ion trap quadrupol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 41 publications
1
18
1
Order By: Relevance
“…Moreover, the contents of phenolic acids and flavonoids in wild rice are significantly higher than that in white rice [23,24]. Plenty of research suggests proanthocyanidins plays a key role in changing the composition of the gut microbiota based on in vitro and in vivo models and the bioactivities of their metabolites [25][26][27]. However, it has not been reported that consumption of WR could prevent MAFLD via the modulation of the gut microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the contents of phenolic acids and flavonoids in wild rice are significantly higher than that in white rice [23,24]. Plenty of research suggests proanthocyanidins plays a key role in changing the composition of the gut microbiota based on in vitro and in vivo models and the bioactivities of their metabolites [25][26][27]. However, it has not been reported that consumption of WR could prevent MAFLD via the modulation of the gut microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, limited information is available on wrinkle formation through ROS generation and lysosomal exocytosis by UVA irradiation compared with wrinkle formation by UVB irradiation. In addition to the known antioxidant effects of ZLE [ 38 ], it also showed an antiwrinkle effect on UVB-irradiated HDFs and SKH-1 hairless mice by blocking the MAPK signaling pathway resulting in the inhibition of NF-κB and activator protein-1 (AP-1) activities [ 18 , 19 ]. Both ZLE and tricin treatments showed skin protective effects and helped reduce wrinkle formation in UVA-irradiated human dermal fibroblasts and hairless mice in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results using polyethylene glycol resin column were achieved by Sasaki et al [ 38 ], who obtained fractions of mixed procyanidins. Chu et al (2018) [ 39 ] compared the separation efficacy of procyanidins and flavonoid glycosides using six different macroporous resins. Other classical techniques such as thin-layer chromatography and column chromatography have been reported but several disadvantages have been identified, such as time-consuming, secondary pollution, complex process, irreversible adsorption on the solid-phase materials, low yield, and high-cost [ 40 ].…”
Section: Introductionmentioning
confidence: 99%